Audiovisual and Roleplay Education Improves Hand Washing Knowledge and Skills in School-Age Children - Maulidya Aisyah Kusuma Dewi; Indriatie Indriatie; Sari Luthfiyah; Joko Suwito (International Journal of Advanced Health Science and Technology, 2025)
Hand washing with soap is essential in preventing infections among school-aged children. Engaging educational methods such as audiovisual media and roleplay can improve children's knowledge and skills in proper hand hygiene. This study aimed to compare the effectiveness of audiovisual and roleplay-based education on hand washing knowledge and skills. A quasi-experimental design with a two-group pre-test post-test was conducted on 48 students at MINU Lumpur Gresik, selected by simple random sampling. Results showed significant improvement in both groups after the intervention (p < 0.05). Audiovisual education improved knowledge, while roleplay enhanced practical skills. No significant difference was found between the two methods overall. Both methods are effective in promoting hand washing behavior among children. This implies that either method can be integrated into school health programs to support hygiene education.